MEDICAL BIOCHEMISTRY AS A MONOVALENT SPECIALIZATION IN THE REPUBLIC OD MACEDONIA - PRESENT SITUATION - Bogdanska, Jasna; Topuzovska, Sonja; Krstevska, Marija; Trajkovska, Katerina Toshevska; Labudovic, Danica; Cekovska, Svetlana (Journal of Morphological Sciences; Vol 1 No 2 (2018): JMS, 2018)
Clinical Chemistry (Medical Biochemistry) practice as a subdiscipline of laboratory medicine in the Republic of Macedonia is regulated by the Ministry of Health according to the Law on Health Protection of the Republic of Macedonia, and was established for the first time in 1960.The four year Specialization Syllabus according to the EU4 Directive was introduced in 2008 and is still in force. Eligible to enter the specialization program are medical doctors and pharmacists. Completing the specialization program and the final exam are requirements for issuing the license for independent clinical chemistry practice by the Macedonian Doctorâ€™s Chamber.The common training meets the requirements for the perspective professional movements across EU borders for the medical doctors and pharmacists (the length of total education is 10 years). In the era of the new analytical techniques, use of statistics, it will be of a great importance to update the present syllabus according to the fifth version of the European Syllabus for post graduate training for specialists in Laboratory Medicine and the needs of our country. The revised training program should call attention towards the structure of the program, as well as towards the expected responsibilities of trainees and trainers and the strategies of our country. The Medical Faculties providing the training in medical biochemistry in the Republic of Macedonia, as well as the professional societies should be included in updating the syllabus in order to have equally trained professionals who can face the new requirements in laboratory medicine in the Republic, but also qualified specialists prepared for the free movement across the European Union borders in the future.  Key words: medical biochemistry, specialization syllabus, vocational training, examination, registration, continues medical education, accreditation